STUDI KEMAMPUAN MENYELESAIKAN SOAL-SOAL FISIKA MENURUT LANGKAH PEMECAHAN MASALAH POLYA PADA PESERTA DIDIK XI IPA SMA NEGERI 1 BARAKA KABUPATEN ENREKANG - Muhammad Sugiarto; Ahmad Yani; Bunga Dara Amin (Universitas Negeri Makassar, 2016)
This research is a descriptive research that aims to obtain a description / level of ability on solving physics’ questions by Problem Solving of Polya steps. The population and the sample in this research were students of class XI IPA SMAN 1 Baraka Enrekang year 2015/2016 year that consist of 101 people. Instruments that used in this research is test of ability on solving physics’ questions by Problem Solving of Polya steps which have valid and reliable to use. Descriptive analysis shows that score of abilty on solving physics’ question by Problem Solving of Polya steps overall in the middle category by percentage of 44,70% and the score of abilitiy on solving physics’ questions by Problem Solving of Polya steps on each sub-indicators obtain indicator,